Cervical Spine Deformity in Long-Standing, Untreated Congenital Muscular Torticollis. Issue 1 (January 2017) - Hussein, Mohammed Ahmed; Yun, In Sik; Park, Hanna; Kim, Yong Oock
Abstract : Background: Congenital muscular torticollis (CMT) is a benign condition. With early diagnosis and appropriate management, it can be cured completely, leaving no residual deformity. However, long-standing, untreated CMT can lead to permanent craniofacial deformities and asymmetry. Methods: Four adult patients presented to the author with long-standing, untreated CMT. Initial clinical assessment demonstrated tightness of the sternocleidomastoid muscle on the affected side. Investigation of cervical spine using 3-dimensional computed tomography scans with cervical segmentation allowed a 3-dimensional module to be separately created for each vertebra to detect any anatomical changes. Results: A change in the axis of the vertebral column was noted when compared to that of the skull. Also, there were apparent anatomical changes affecting the vertebrae, which were most noticeable at the level of the atlas and axis vertebrae. These changes decreased gradually till reaching the seventh cervical vertebra, which appeared to be normal in all patients. The changes in the atlas vertebra were mostly due to its intimate relation with the skull base. The changes of the axis were the most significant, affecting mainly the superior articular facet, the lamina, and the body. Conclusions: There were seemingly permanent changes along the cervical spine region in the adult patients with long-standing, untreated CMT in the form of bending and rotation deformities that might result in residual torticollis postoperatively.